Research Foundations for Evidence-Informed Early Childhood Intervention Performance Checklists - Carl J. Dunst (MDPI AG, 2017)
The research evidence for early childhood intervention practices performance checklists is described. Performance checklists include lists of the tasks or steps required to complete a practice competently. The checklists were developed using a conceptualization-operationalization-measurement framework where findings from research syntheses and empirical studies informed the selection or development of checklist indicators. This paper includes a meta-review of empirical evidence demonstrating practice-outcome relationships consistent with the purposes and goals of each of the performance checklists. Findings from more than 200 narrative reviews, meta-analyses, integrative reviews, and other types of research syntheses were the sources of evidence and foundations for 26 early childhood intervention performance checklists. The research evidence, taken together, indicates that the checklist indicators have a substantial evidence base for each of the performance checklist practices. Strengths and limitations of the meta-review are described.